Pacifier Overuse and Conceptual Relations of Abstract and Emotional Concepts - Barca, Laura; Mazzuca, Claudia; Borghi, Anna M. (Frontiers in Psychology, 2017)
This study explores the impact of the extensive use of an oral device since infancy (pacifier) on the acquisition of concrete, abstract and emotional concepts. While recent evidence showed a negative relation between pacifier use and children's emotional competence (Niedenthal et al., 2012; 2014), the possible interaction between use of pacifier and processing of emotional and abstract language has not been investigated. According to recent theories, while all concepts are grounded in sensorimotor experience, abstract concepts activate linguistic and social information more than concrete ones. Specifically, the Words As Social Tools (WAT) proposal predicts that the simulation of their meaning leads to an activation of the mouth (Borghi & Binkofski, 2014; Borghi & Zarcone, 2016). Since the pacifier affects facial mimicry forcing mouth muscles into a static position, we hypothesize its possible interference on acquisition/consolidation of abstract emotional and abstract non emotional concepts, which are mainly conveyed during social and linguistic interactions, than of concrete concepts. 59 first grade children, with a history of different frequency of pacifier use, provided oral definitions of the meaning of abstract, abstract emotional and concrete words. Main effect of concept type emerged, with higher accuracy in defining concrete and abstract emotional concepts with respect to abstract concepts, independently from pacifier use. Accuracy in definitions was not influenced by the use of pacifier, but correspondence and hierarchical clustering analyses suggest that the use of pacifier differently modulates the conceptual relations elicited by abstract emotional and abstract concepts. While the majority of the children produced a similar pattern of conceptual relations, analyses on the few (6) children who overused the pacifier (for more than three years) showed that they tend to distinguish less clearly between concrete and abstract emotional concepts and between concrete and abstract non emotional concepts than children who did not use it (5) or used it for short (17). As to the conceptual relations they produced, children who overused the pacifier tended to refer less to their experience and to social and emotional situations, use more exemplifications and functional relations, and less free associations.